Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada CV Kembar Jaya Parung - Ahmad Farhan Kuncoro; Retno Japanis Permatasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the influence of leadership style and physical work environment on employee performance at CV Kembar Jaya Parung both partially and simultaneously on the processing of empirical data from the dissemination of questionnaires that have been carried out. The method used in this study is a quantitative method using a sample determination technique of 75 respondents. In this study, data analysis techniques are used in the form of: validity testing, reality testing, normality testing, classical assumption testing, quantitative testing and hypothesis testing. It can be known that the result of the multiple linear regression equation obtained between Y = 7.537 + 0.382 (X1) + 0.357 (X2). This is evidenced by the results of hypothesis tests based on the simultaneous obtained F value calculated > F table or (80.684 > 3.120), this is also strengthened by the significance of < 0.050 or (0.000 < 0.050). The results of the determination coefficient test of the leadership style variable (X1) and the physical work environment (X2) had an influence of 69.1 % on the performance of CV Kembar Jaya Parung. Thus, H0 rejected H3 accepted can be interpreted that there is a simultaneous significant influence between leadership style (X1), physical work environment (X2) and employee performance (Y)